Pengaruh Pemanfaatan Youtube Edukasi Terhadap Motivasi Belajar Siswa - Didit Darmawan; Vina Maulidatul Lailiyah (Indo-MathEdu Intellectuals Journal, 2026)
The development of digital technology has brought significant changes to the world of education, particularly through the use of multimedia-based media such as YouTube, podcasts, and online learning platforms. YouTube has become a widely used medium in the learning process because it can present material in an audio-visual, interactive, and easily accessible manner for students. This study aims to analyze the effect of the use of educational YouTube on student learning motivation. The study used a descriptive qualitative approach with a literature review method (library research). Data were obtained from scientific articles, books, and previous research results relevant to the use of YouTube in learning and student learning motivation. Data analysis was carried out through the stages of source identification, literature selection based on topic relevance, content evaluation, and conceptual synthesis to find patterns of relationships between the use of educational YouTube and student learning motivation. The results of the study indicate that educational YouTube not only functions as a medium for delivering material but also as a tool capable of increasing student attention, engagement, and interest in learning through the presentation of visual, flexible, and contextual content. Conceptually, the use of YouTube encourages the formation of more interactive and student-centered learning, thereby contributing to increased intrinsic and extrinsic motivation in the learning process.